Patent Law And Access To Biotechnology - Otim, Enoch (Technology and Economics Law Journal, 2024)
The research analyzes the use of patents in a field other than industry and how they have a wider impact than the monetary gain of the patent holder. In recent years, patents have been taken out on organisms and gene sequences, which has a flow-on effect of jeopardizing any further research in that area and possible future developments. This is a serious issue in the fast-moving field of medical biotechnology. For example, researchers patented and developed a test that utilized and identified a gene sequence that was later patented by another party. The researchers may have to discontinue the test due to the risk of patent infringement. The development of new technologies and useful products is encouraged by the patent system; however, patents on gene sequences and organisms are too wide-reaching and generally obstruct further research in the same area. This is a big contrast from the original purpose of the patent law. To provide insight into the complex relationship between patent law and biotechnology, the paper will first provide a brief overview of why and how patent law came about to show the contrast in reasons why it was originally used and the way it is used today. The paper will then consider the different economic and social impacts that patents can have on the public surrounding medical biotechnology. Finally, a brief overview will be presented on the current view of biotechnology patents in international law and the upcoming changes that will serve to solve the problems outlined in this paper.